Neural Correlates of Decisions in Quasi-Realistic, Affective Social Interactions in Individuals With Violence-Related Socialization - Wiechert, Juliana; Janzen, Axel; Achtziger, Anja; Fehr, Thorsten (Frontiers in Behavioral Neuroscience, 2021)
Appropriate social behavior in aggressive-provocative interactions is a prerequisite for a peaceful life. In previous research, the dysfunctions of the control of aggression were suggested to be modulated by enhanced bottom-up (sub-cortically driven) and reduced top-down (iso-cortical frontal) processing capability. In the present study, two groups of individuals with enhanced (EG) and normal (NG) experiences of violent acts during their socialization made binary behavioral decisions in quasi-realistic social interactions. These interactions were presented in short video clips taken from a first-person perspective. The video clips showed social interaction scenarios oriented on realistic everyday life situations. The behavioral data supported the distinct affective qualities of three categories of social interactions. These categories were labeled as aggressive–provocative, social–positive, and neutral–social interactions. Functional neuroimaging data showed extended activation patterns and higher signal intensity for the NG compared to the EG in the lateral inferior frontal brain regions for the aggressive provocative interactions. Furthermore, the peri-aqueductal gray (PAG) produced enhanced activations for the affective interaction scenarios (i.e., aggressive-provocative and social-positive) in both groups and as a trend with the medium effect size for the neutral interactions in the EG. As the individuals in the EG did not show open aggression during the functional MRIA (fMRI) investigation, we concluded that they applied individual self-control strategies to regulate their aggressive impulses immediately. These strategies appeared to be top-down regulated through the dorsal frontal brain areas. The predominant recruitment of the heteromodal cortices during the neural processing of complex social interactions pointed to the important role of the learning history of individuals and their socialization with differing levels of violent experiences as crucial modulators in convicts. Our data suggest that building or strengthening the association between prototypical social contexts (e.g., aggressive-provocative interactions) and appropriate behaviors as a response to it provides a promising approach to successfully re-socialize people with a delinquent history.